PENGEMBANGAN PEMBELAJARAN QUR’AN HADITS BERBASIS PROBLEM POSING DALAM MENINGKATKAN KREATIVITAS SISWA - Syaiful Rohman; Ishaq Syahid (JEMI, 2024)
In this research there are three problem formulations, namely: 1) What is the process of developing Islamic education learning based on problem posing in increasing the creativity of basic education students at MI Nurul Karomah. 2) What is the validity and practicality of developing Islamic education learning based on problem posing in increasing the creativity of basic education students. 3) How is student creativity after learning problem posing in basic education. This type of research is development research because the aim of this research is to produce learning tools in the form of lesson plans and worksheets. This development research uses the Thiagarajan design model. The Thiagarajan model consists of 4 stages known as the 4-D model (four D model). The four stages are the definition stage, design stage, development stage and disseminate stage. To obtain research data, 5 data collection techniques were used, namely: interviews, expert validation, observation, questionnaires and tests. Interviews were used to obtain data about the problem posing-based Islamic education learning development process. Expert validation is used to obtain data about the validity and practicality of the lesson plan and student worksheet. Observation is used to obtain data during the testing process which includes student activities, implementation of lesson plan syntax, and observation of student creativity. Student response questionnaires were used to obtain data during the trial process. The research data was analyzed and the results obtained showed that the lesson plan and student worksheet could be categorized as valid and practical so they were suitable for use. Meanwhile, student creativity based on the results of the pre-test and post-test shows that the creativity of medium and high students has increased in the post test.Keywords: Student creativity, problem posing learning.